AI-powered discovery of a novel p53-Y220C reactivator - Zhou, Shan; Chai, Dafei; Wang, Xu; Neeli, Praveen; Yu, Xinfang; Davtyan, Aram; Young, Ken; Li, Yong (Frontiers in Oncology, 2023)
Introduction The p53-Y220C mutation is one of the most common mutations that play a major role in cancer progression. Methods In this study, we applied artificial intelligence (AI)-powered virtual screening to identify small-molecule compounds that specifically restore the wild-type p53 conformation from p53-Y220C. From 10 million compounds, the AI algorithm selected a chemically diverse set of 83 high-scoring hits, which were subjected to several experimental assays using cell lines with different p53 mutations. Results We identified one compound, H3, that preferentially killed cells with the p53-Y220C mutation compared to cells with other p53 mutations. H3 increased the amount of folded mutant protein with wild-type p53 conformation, restored its transcriptional functions, and caused cell cycle arrest and apoptosis. Furthermore, H3 reduced tumorigenesis in a mouse xenograft model with p53-Y220C-positive cells. Conclusion AI enabled the discovery of the H3 compound that selectively reactivates the p53-Y220C mutant and inhibits tumor development in mice.